ELECTRICAL STORMS AND THEIR PROGNOSTIC IMPLICATIONS - Awan, Zahid Aslam; Hassan, Mahmood ul; Bangash, Kamran; Shah, Bakhtawar; Noor, Lubna (Journal of Ayub Medical College Abbottabad, 2009)
Background: Prevention of sudden cardiac death has always been a challenge for electrophysiologists and to date, automatic implantable cardiovertor defibrillator (AICD) is found to be the only remedy. This device delivers an intracardiac shock whenever it senses a fatal ventricular arrhythmia in order to achieve sinus rhythm. If the delivery of these intracardiac shocks becomes frequent, the situation is declared as an electrical storm. This article deals with the frequency, precipitating factors and prevention of electrical storms. Methods: One hundred and ten episodes of electrical storms (a total of 668 shocks) were retrospectively analysed in 25 recipients of automatic implantable cardioverter defibrillators. ECG, echocardiography, serum electrolytes, urea and creatinine were done for all the patients, and they were hospitalized for a minimum of 24 hours. Results: During the 3 year study period, all the 25 patients with an implantable cardiovertor defibrillator, on an average, received one shock per two years. However, 12 out of these 25 patients (50%) had more than two shocks within 24 hours. Most of these patients with electrical storms were having active ischemia, electrolytes imbalances or renal failure. Conclusion: Electrical storms are common in patients with coronary artery disease with impaired left ventricular functions. Ischemia, electrolytes imbalances and renal failure predispose to the electrical storms. Electrical Storms are predictors of poor prognosis. Keywords: Electrical Storm (ES), Automatic Implantable Cardiovertor Defibrillator (AICD), Ventricular Tachycardia (VT), Ventricular Fibrillation (VF)